Subradiance protected excitation transport - Needham, Jemma Ann (2020)
We investigate collective behaviour that appears in open, many-body systems of two- and four-level atoms. Here, ``open" refers to the system interacting with an external environment that causes dissipation. We derive a general open quantum master equation to describe the system dynamics only, independent of this environment. We identify processes such as coherent exchange of virtual photons and modified decay rates caused by long-range interactions between all pairs of atoms that scale with distance by inverse power laws.